Desenvolvimento de metodologias em síntese orgânica: uso do catalisador Eu-MOF na síntese de cianoidrinas e obtenção de anéis tetraidropirânicos utilizando [BIMIM][PF6] - Batista, Poliane Karenine (2017)
Currently several works have been developed in order to provide alternative routes for the synthesis of several organic compounds. These new protocols are generally aimed at obtaining softer and more eco-friendly reactive conditions, better yields and / or reactional times, and mechanistic studies, among others. This work consists of the study of synthesis routes of cyanohydrins and tetrahydropyrans, using lanthanide catalysts and ionic liquids, respectively. As cyanohydrins are products that can be transformed into important organic intermediates. They are obtained by the cyanosilylation of aldehydes reaction, which is synthetically viable only in the presence of a Lewis acid. In this work, the MOF [Eu2 (MELL)(H2O)6] was used as a heterogeneous catalyst in the cyanosilylation of aldehydes reaction. The catalytic assays were optimized using a thermally activated MOF in acetonitrile. Different aldehydes several structurally provided their respective cyanohydrins ranging from 1 to 6 hours and yields of 62 to 100%. The MOF was recycled in the addition reaction of TMSCN to 2-furfuraldehyde without loss of activity for five cycles. Tetrahydropyran rings (THP) are common in many natural products, so various strategies are being developed to synthesize them. In this work we also describe the study to obtain 2,4,6-trisubstituted tetrahydropyrans in a single step promoted by the ionic liquid (IL) BMIM][PF6] between the allyl bromide and aldehydes, through the Barbier-Prins reaction. The tests were performed under different conditions and optimized using 1: 4 benzaldehyde and allyl bromide. The use of IL [BMIM][PF6] provided THPs of various aldehydes in good yields ranging from 40% to 75% in 8 hours of reaction. In addition, IL [BMIM][PF6] was recovered and reused in the preparation of 4-bromo-2,6-diphenyl-tetrahydro-2H-pyran by up to 5 times without significant loss of yield of that product. The influence of the PF6- anion on the reaction between benzaldehyde and allyl bromide under the Barbier reaction conditions was investigated, as well as the influence of SnBr2 salt on the Prins cyclization reaction between homoallylic alcohol and benzaldehyde. The results show evidence that PF6- acts by accelerating the Barbier reaction and the excess of SnBr2 acts as Lewis acid in the Prins cyclization reaction. Subsequently, the use of KI in the reaction between benzaldehyde and allyl bromide was investigated, and it was found that depending on the ratio used between KI and SnBr2, the preferential formation of homoalyl alcohol or THP compound could occur.